Niobium oxyhydroxide as a bioactive agent and reinforcement to a high-viscosity bulk-fill resin composite - Alyssa Teixeira OBEID; Tatiana Rita de Lima NASCIMENTO; Ana Carolina AGASSI; Ana Zélia Falcão ALMEIDA; Ana Paula de Melo Alves GUEDES; João Marco ALVES; Juliana Fraga Soares BOMBONATTI; Marilia Mattar de Amoêdo Campos VELO (University of São Paulo, 2024)
Abstract Objective The present in vitro study incorporated niobium oxyhydroxide fillers into an experimental high-viscosity bulk-fill resin composite to improve its mechanical performance and provide it a bioactive potential. Methodology Scanning electron microscopy synthesized and characterized 0.5% niobium oxyhydroxide fillers, demonstrating a homogeneous morphology that represented a reinforcement for the feature. Fillers were weighed, gradually added to the experimental resin composite, and homogenized for one minute, forming three groups: BF (experimental high-viscosity bulk-fill resin composite; control), BF0.5 (experimental high-viscosity bulk-fill resin composite modified with 0.5% niobium oxyhydroxide fillers), and BFC (commercial bulk-fill resin composite Beautifil Bulk U, Shofu; positive control). In total, 10 specimens/groups (8 × 2 × 2 mm) underwent flexural strength (FS) tests in a universal testing machine (Instron) (500N). Resin composites were also assessed for Knoop hardness (KH), depth of cure (DoC), degree of conversion (DC), elastic modulus (E), and degree of color change (ΔE). The bioactive potential of the developed resin composite was evaluated after immersing the specimens into a simulated body fluid in vitro solution and assessing them using a Fourier-transformed infrared spectroscope with an attenuated total reflectance accessory. One-way ANOVA, followed by the Tukey's test (p<0.05), determined FS, DC, KH, and ΔE. For DoC, ANOVA was performed, which demonstrated no significant difference between groups (p<0.05). Conclusions The high-viscosity bulk-fill resin composite with 0.5% niobium oxyhydroxide fillers showed promising outcomes as reinforcement agents and performed well for bioactive potential, although less predictable than the commercial resin composite with Giomer technology.